Comparison of the Efficacy between Bilateral Ultrasound Guided Erector Spinae Block versus Incision Site Infiltration for Duration of Analgesia in Lumbar Spinal Surgery Using Levobupivacaine: A Prospective, Randomized Comparative Study - Karthik G Sheshadri; Sudheer Ramegowda; Mahesh Chandra; Prajyot Bhurli; Ashwani Kristipati; Renjan R I (Archives of Anesthesia and Critical Care)
Background: There are increasing number of patients undergoing lumbar spine surgeries. Many modalities have been developed to manage post operative pain. More recently, erector spinae plane blocks found to be effective in reducing post operative pain. The purpose of this study was to compare the analgesic efficacy of ultrasound guided Erector spinae block with wound infiltration using levobupivacaine in lumbar spine surgeries under general anaesthesia. Methods: A prospective randomized single blinded study was carried out in 50 patients of ASA grade I and II, aged 20 to 60 years scheduled for elective lumbar spine surgeries. Under USG guidance, group A received bilateral erector spinae block at L2 with 20 ml of 0.125% levobupivacaine on each side and Group B received incision site infiltration with 40 ml 0.125% levobupivacaine. Patients were evaluated primarily for duration of analgesia using VAS score. Results: Both groups were statistically comparable with respect to all demographic variables, ASA grading and duration of surgery. The duration of analgesia was prolonged in group A when compared to group B (496 ± 36.2 v/s 55±10.6) (P=0.0016). VAS score and total rescue analgesia requirement were higher in group B. Conclusion: Erector spine block is more effective in providing post-operative analgesia compared to local site infiltration in patients undergoing spine surgeries following general anaesthesia using Inj Levobupivacaine 0.125% as local anaesthetic.